La expropiación de bienes inmuebles, una limitación al derecho de propiedad - Cabezas Endara, Marcia Elizabeth (2016)
The present thesis tries on a special type of expropriation that settles down in the Organic Code of Territorial Organization, Autonomy and Decentralization in favor of the governments decentralized autonomous metropolitan and municipal that is based in the regulation of population establishments in the urban sector and of urban development. To the moment that it is carried out on the part of the administrative entity the declaration of public utility or of social interest, it should be carried out the payment of the fair price that consists according to the update commercial value that consists in the respective municipality or metropolitan district, for that which should be carried out a negotiation with the proprietor, and in the event of not reaching an agreement it will think about the expropriation judgment. In this new expropriation class for the regularization of urban establishments, be believed in the law an economic serious damage to the proprietor as a consequence of that the payment of the fair price (compensation for expropriation) will make it to him for dividends or biannual quotas, to a term that could extend up to 25 years, with that which the holder of the domain of the property affected by the public utility, doesn't recover the value of his property, being a totally prejudicial disposition to the right to the private property. As it has come being in the history of our legislation, the payment of the fair price of a property in expropriation process for public utility or social interest, the payment has always corresponded to the administrative entity, that which stays in the general dispositions on expropriation that determines the organic Code of Territorial Organization, Autonomy and Decentralization, when settling down that one of the requirements for the declaration of public utility budgetary certification is attached that guarantees the payment to the proprietor. The problem arises that in the Special Expropriation for the Regularization of Urban Establishments, it has particular norms that attempt against the right of property of the holder of the property, since the budgetary (indispensable requirement) certification is substituted, for a financing plan in charge of the benefiters (population to be regularized), that is to say, the autonomous municipal government or subway doesn't cancel the fair price directly, but rather the payment makes it the benefiters in comfortable dividends, causing a serious damage to the proprietor while the administration has not canceled any value for such a concept. This juridical problem is of vital importance and it requires to be analyzed and reformed, always in search of the interest of all the people, that is to say so much of the benefiters of the very condemned as of the domain holder.